(untitled) (Journal of Insurance Studies in South Asia, 2024)
This study delves into the emerging challenges encountered within the motor insurance sector of Nepal, focusing on issues faced by the marketing, underwriting, and claims departments. With the backdrop of regulatory directives guiding motor insurance policies, including the mandatory requirement of third-party coverage, this research explores the dynamics influencing the distribution, assessment, and settlement of motor insurance policies. Through a theoretical framework highlighting perceived attributes, perceived risk, and compatibility, alongside insights from existing literature, the study aims to elucidate the intricacies of challenges faced by the industry. Employing a mixed-method approach involving semi-structured interviews and questionnaires, data was gathered from a diverse sample representing different stages of the insurance process. Analyzing responses from 60 participants, the study reveals nuanced challenges in marketing, underwriting, and claims departments. The findings underscore the significance of addressing these challenges to enhance operational efficiency and customer satisfaction within the motor insurance sector of Nepal.